Associations between degrees of task delegation and job satisfaction of general practitioners and their staff: a cross-sectional study. Issue 1 (December 2017) - Riisgaard, Helle; Søndergaard, Jens; Munch, Maria; Le, Jette; Ledderer, Loni; Pedersen, Line; Nexøe, Jørgen
Abstract Background In recent years, the healthcare system in the western world has undergone a structural development caused by changes in demography and pattern of disease. In order to maintain the healthcare system cost-effective, new tasks are placed in general practice urging the general practitioners to rethink the working structure without compromising the quality of care. However, there is a substantial variation in the degree to which general practitioners delegate tasks to their staff, and it is not known how these various degrees of task delegation influence the job satisfaction of general practitioners and their staff. Methods We performed a cross-sectional study based on two electronic questionnaires, one for general practitioners and one for their staff. Both questionnaires were divided into two parts, a part exploring the degree of task delegation regarding management of patients with chronic obstructive pulmonary disease in general practice and a part concerning the general job satisfaction and motivation to work. Results We found a significant association between perceived "maximal degree" of task delegation in management of patients with chronic obstructive pulmonary disease and the staff's overall job satisfaction. The odds ratio of the staff's satisfaction with the working environment displayed a tendency that there is also an association with "maximal degree" of task delegation. In the analysis of the general practitioners, the odds ratios of the results indicate that there is a tendency that "maximal degree" of task delegation is associated with overall job satisfaction, satisfaction with the challenges in work, and satisfaction with the working environment. Conclusions We conclude that a high degree of task delegation is significantly associated with overall job satisfaction of the staff, and that there is a tendency that a high degree of task delegation is associated with the general practitioners' and the staff's satisfaction with the working environment as well as with general practitioners' overall job satisfaction and satisfaction with challenges in work. To qualify future delegation processes within general practice, further research could explore the reasons for our findings.